Call volume, triage outcomes, and protocols during the first wave of the COVID‐19 pandemic in the United Kingdom: Results of a national survey. Issue 4 (2nd August 2021) - Snooks, Helen; Watkins, Alan John; Bell, Fiona; Brady, Mike; Carson‐Stevens, Andy; Duncan, Edward; Evans, Bridie Angela; England, Louise; Foster, Theresa; Gallanders, John; Gunson, Imogen; Harris‐Mayes, Robert; et al.
Abstract: Objectives: During the first wave of the COVID‐19 pandemic in the United Kingdom (UK), to describe volume and pattern of calls to emergency ambulance services, proportion of calls where an ambulance was dispatched, proportion conveyed to hospital, and features of triage used. Methods: Semistructured electronic survey of all UK ambulance services (n = 13) and a request for routine service data on weekly call volumes for 22 weeks (February 1–July 3, 2020). Questionnaires and data request were emailed to chief executives and research leads followed by email and telephone reminders. The routine data were analyzed using descriptive statistics, and questionnaire data using thematic analysis. Results: Completed questionnaires were received from 12 services. Call volume varied widely between services, with a UK peak at week 7 at 13.1% above baseline (service range ‐0.5% to +31.4%). All services ended the study period with a lower call volume than at baseline (service range ‐3.7% to ‐25.5%). Suspected COVID‐19 calls across the UK totaled 604, 146 (13.5% of all calls), with wide variation between services (service range 3.7% to 25.7%), and in service peaks of 11.4% to 44.5%. Ambulances were dispatched to 478, 638 (79.2%) of these calls (service range 59.0% to 100.0%), with 262, 547 (43.5%) resulting in conveyance to hospital (service range 32.0% to 53.9%). Triage models varied between services and over time. Two primary call triage systems were in use across the UK. There were a large number of products and arrangements used for secondary triage, with services using paramedics, nurses, and doctors to support decision making in the call center and on scene. Frequent changes to triage processes took place. Conclusions: Call volumes were highly variable. Case mix and workload changed significantly as COVID‐19 calls displaced other calls. Triage models and prehospital outcomes varied between services. We urgently need to understand safety and effectiveness of triage models to inform care during further waves and pandemics.